The Roles of the Cortical Motor Areas in Sequential Movements - Ohbayashi, Machiko (Frontiers in Behavioral Neuroscience, 2021)
The ability to learn and perform a sequence of movements is a key component of voluntary motor behavior. During learning of sequential movements, individuals go through distinct stages of performance improvement. For instance, sequential movements are initially learned relatively fast and later learned more slowly. Over multiple sessions of repetitive practice, performance of the sequential movements can be further improved to the expert level and maintained as a motor skill. How the brain binds elementary movements together into a meaningful action has been a topic of much interest. Studies in human and non-human primates have shown that a brain-wide distributed network is active during the learning and performance of skilled sequential movements. The current challenge is to identify a unique contribution of each area to the complex process of learning and maintenance of skilled sequential movements. Here, I bring together the recent progress in the field to discuss distinct roles of cortical motor areas in this process.